Lipid profiles in smoking and non-smoking male adolescents - Sigit Prastyanto; Mei Neni Sitaresmi; Madarina Julia (Indonesian Pediatric Society, 2014)
Background The prevalence of smoking in adolescentstends to increase. Smoking is associated with a higher risk ofdyslipidemia.Objective To compare the lipid profiles of tobacco-smoking andnon-tobacco-smoking male adolescents.Methods We performed a cross- sectional study in three vocationalhigh schools in Yogyakarta from January to April 2011. Dataon smoking status, duration of smoking and number cigarettesconsumed per day were collected by questionnaires. We randomlyselected 50 male smokers and 50 male non-smokers as the studysubjects.Results Mean differences between smokers and non-smokerswere 44.5 (95%CI 28. 7 to 60.1) mg/dL for triglyceride levels; 8.0(95% CI 1.0 to 14.9) mg/dL for low density lipoprotein (LDL)cholesterol; 11.8 (1.1 to 22.4) mg/dL for total cholesterol and -5.7mg/dL (95% CI -8.8 to -2.6) for high density lipoprotein (HDL)cholesterol. Mean differences (95% CI) between smokers whohad engaged in smoking for > 2 years and those who had smokedfor :S:2 years were -18.1 (95% CI -33 .9 to -2.3) mg/dL for totalcholesterol; -49.4 (95% CI -67.2 to -3 1.5) mg/dL for triglycerides.Mean differences between those who smoked > 5 cigarettes/dayand :s:5 cigarettes per day were -18 .4 (95% CI -32.8 to -4.1) mg/dL for total cholesterol and -29.1 (95% CI -53.6 to -4.6) mg/dLfor triglycerides.Conclusion Smoking more than 5 cigarettes/day significantlyincreases total cholesterol, LDL cholesterol, and triglyceridelevels, as well as reduces HDL cholesterol levels; while smokingmore than 2 years significantly increases total cholesterol andtriglyceride levels